Effectiveness Of BCG Vaccination in Prevention of Childhood Tuberculosis: A Prospective Study from Kishanganj, Bihar - Shahnawaz, Kashif; Sarkar, Goutam; Das, Palash; Basu, Mausumi; Roy, Biman (National Journal of Community Medicine, 2013)
Introduction: BCG vaccine has shown consistently high efficacy against childhood tubercular meningitis and miliary tuberculosis and other mycobacterial diseases. It is considered to be a safe vaccine with a low incidence of adverse effects. Efficacy of BCG vaccine found in different clinical trials is variable in different geography. Objectives: Study was done to assess the efficacy of BCG vaccine. Materials and Methods: All the children who were less than three years of age and were previously BCG vaccinated and not-vaccinated, were included in this study. A total of sixty (60) vaccinated children and sixty non-vaccinated children were selected. These children were followed up prospectively for 24 months, at the end of which, it was seen whether they developed tuberculosis or not. Results: Out of these 60 children in both the cases and control groups, total number of BCG vaccinated children who developed TB were 4 (i.e. 6.6%) and total number of Non-BCG vaccinated children who developed TB were 12 (i.e. 20%). Thus, the efficacy of BCG vaccine calculated in our study was 67%. Conclusion: Most studies in different parts of the world have shown that the efficacy of BCG vaccine varies from zero to eighty percent. This study favors the efficacy of BCG vaccine. This vaccination strategy will be favorable for our children. Creation of awareness among the parents and family members for an early administration of BCG vaccine after child birth can be recommended.